2014
DOI: 10.1021/pr500966h
|View full text |Cite
|
Sign up to set email alerts
|

Metabonomic Profiling of Bladder Cancer

Abstract: Early diagnosis and life-long surveillance are clinically important to improve the long-term survival of bladder cancer patients. Currently, a noninvasive biomarker that is as sensitive and specific as cystoscopy in detecting bladder tumors is lacking. Metabonomics is a complementary approach for identifying perturbed metabolic pathways in bladder cancer. Significant progress has been made using modern metabonomic techniques to characterize and distinguish bladder cancer patients from control subjects, identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 195 publications
0
54
0
Order By: Relevance
“…14 Currently, metabolomics has demonstrated its practicality by the identification of BC biomarkers in urine, 15,16 plasma and tissue samples. 17,18 Additionally, metabolic studies in cell culture are highly valuable 19 as they can identify functional biomarkers that represent cellular processes, 20,21 and/or provide insights into the individuality of various cancer cell lines. 22,23 These are essential for a comprehensive understanding of cancer cell biology and to complement clinical studies.…”
Section: Introductionmentioning
confidence: 99%
“…14 Currently, metabolomics has demonstrated its practicality by the identification of BC biomarkers in urine, 15,16 plasma and tissue samples. 17,18 Additionally, metabolic studies in cell culture are highly valuable 19 as they can identify functional biomarkers that represent cellular processes, 20,21 and/or provide insights into the individuality of various cancer cell lines. 22,23 These are essential for a comprehensive understanding of cancer cell biology and to complement clinical studies.…”
Section: Introductionmentioning
confidence: 99%
“…Investigating potential biomarkers may bring about new breakthroughs in strategies on reducing recurrence and survival rate, similar to the discovery of trastuzumab following studies on the human epidermal growth factor receptor-2 (HER2) studies. Recently, important progress has been made in the biomarker field particularly in new detection techniques in genomics and proteomics (27,28). In bladder cancer, a number of accomplishments were achieved, including the Table II.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies using mass spectrometric (MS) methods reported promising results for bladder cancer (BCa) detection and separation of invasive BCa from non-invasive BCa (Issaq et al, 2008;Huang et al, 2011;Pasikanti et al, 2013;Chan et al, 2015;Zhou et al, 2016). However, cohort sizes were small in most studies and the effects of renal cancer and bladder inflammation were the major problem in BCa detection (Van et al, 2011).…”
Section: Bladder Cancermentioning
confidence: 99%